The Earliest Patristic Interpretations of PSALM 82, Jewish Antecedents, and the Origin of Christian Deification - Mosser, Carl (The journal of theological studies, 2005)
Deification is an important component of patristic theology. Its chief proof-text is Ps. 82:6. It has been commonly assumed that this verse had nothing to do with the origin of the doctrine but was cited later to bolster its biblical warrant. On this view the patristic writers followed Jesus’ precedent (John 10:34–5) and cited Ps. 82:6 for its declaration of godhood. However, close examination of the earliest extant interpretations of Psalm 82 in Justin Martyr, Irenaeus, and Clement of Alexandria demonstrates that the chief significance of the psalm was its declaration of divine sonship. The psalm was understood to predict distinctive aspects of Pauline and Johannine soteriology. Moreover, patristic interpretations adapted antecedent traditions that read Ps. 82:1, 6–7 as summarizing salvation history from Adam's fall to the eschatological restoration of the immortality and glory he lost. Elements of this tradition are attested in 11QMelchizedek, the Gospel of John, and other Second Temple and Rabbinic Jewish texts. Rather than being the climax of the Hellenization of Christianity as Harnack asserted, the doctrine of deification expressed in the earliest patristic interpretations of Psalm 82 represents a remarkable instance of fidelity to the Second Temple Jewish roots of Christian belief.